MIKR (Militant, Intellectual, Competitive, Regenerative) Theory In The Concept Of Developing A Company - Yasmin, Alfina; Hidayat, Indriyanti (Pascasarjana STIE Miftahul Huda, 2024)
This research study examines the MIKR theory which is an acronym for Militant, Intellectual, Competitive, and Regenerative. This theory is an important foundation in the development of quality modern human resources. This study uses a qualitative research method with a literature study approach to analyze each MIKR component in depth. The results of the study show that these four elements are interrelated and form a solid foundation in the formation of superior individual characters. This study also identifies that the implementation of MIKR requires a systematic and structured approach, taking into account contextual factors such as organizational culture, level of HR maturity, and dynamics of the external environment. The main challenges in implementation include resistance to change, the need for substantial resources, and the complexity of measuring effectiveness.